QM/MM Study of the Reaction Mechanism of Thermophilic Glucuronoyl Esterase for Biomass Treatment. Issue 20 (4th August 2022) - Viegas, Matilde F.; Neves, Rui P. P.; Ramos, Maria J.; Fernandes, Pedro A.
Abstract: Hydrolysis of lignocellulosic biomass, composed of a lignin‐carbohydrate‐complex (LCC) matrix, is critical for producing bioethanol from glucose. However, current methods for LCC processing require costly and polluting processes. The fungal Thermothelomyces thermophila glucuronoyl esterase (TtGE) is a promising thermophilic enzyme that hydrolyses LCC ester bonds. This study describes the TtGE catalytic mechanism using QM/MM methods. Two nearly‐degenerate rate‐determining transition states were found, with barriers of 16 and 17 kcal ⋅ mol −1, both with a zwitterionic nature that results from a proton interplay from His346 to either the Ser213‐hydroxyl or the lignin leaving group and the rehybridisation of the ester moiety of the substrate to an alkoxide. An oxyanion hole, characteristic of esterases, was provided by the conserved Arg214 through its backbone and sidechain. Our work further suggests that a mutation of Glu267 to a non‐negative residue will decrease the energetic barrier in ca. −5 kcal ⋅ mol −1, improving the catalytic rate of TtGE. Abstract : Two nearly degenerate rate‐limiting transition states (16 and 17 kcal ⋅ mol −1 ), bridged by a zwitterionic tetrahedral intermediate stabilized by an oxyanion from Arg271, were found for the acylation of hemicellulosic biomass by glucuronoyl esterase, by QM/MM calculations. The mutation of the Glu267 near the negatively charged acylated intermediate was proposed to favor catalysis by the enzyme.